Efforts to Overcome Adolescent Academic Anxiety through Intervention Programs with a Cognitive-Behavioral Therapy Approach - Sekarini Andika Permatasari; Wuri Prasetyawati (Bisma The Journal of Counseling, 2023)
Academic anxiety is an anxious response that arises due to a maladaptive mindset in doing academic assignments. Academic anxiety in adolescence that is not handled properly can interfere with students in the academic field and everyday life. Thus, interventions are needed to help students overcome their anxiety problems. This study aims to see the effectiveness of individual intervention programs with the CBT approach in dealing with academic anxiety in adolescent students. This research is a quasi-experimental study with a single-subject design. The subject is a 14-year-old female student. Data collection in the study was carried out using observation and interview methods, with research instruments in the form of observation guidelines. Measuring tools used are the Coping Questionnaire-Child and The Subjective Units of Distress/Discomfort Scale to measure the subject's perception of his ability to overcome anxiety and assess the level of anxiety experienced. Data were analyzed using visual inspection drawn from graphs. The results showed that individual intervention programs using the CBT approach effectively increased the ability of subjects with academic anxiety to overcome their anxiety.